2010
DOI: 10.1007/s12206-010-0711-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxy-fuel combustion boiler for CO2 capturing: 50 kW-class model test and numerical simulation

Abstract: A novel oxy-fuel burner was devised and integrated into a 50 kW-class furnace-type boiler system. A series of experiments was conducted to verify its feasibility for industrial applications. Additionally, numerical simulations were performed and the results validated against experimental data on the detailed physics inside the conventional-design combustion chamber. The oxy-fuel burner, with the help of gas radiation, could effectively heat the combustion chamber. The composition of the exhaust gas revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In a study on applying oxy-fuel combustion to an industrial boiler, Ahn et al [16] compared air combustion and oxy-fuel combustion in the combustion chamber of a furnace-type boiler and showed that retrofitting was possible by replacing the burner. Introducing flue gas recirculation (FGR) into an oxy-fuel boiler offers several benefits, including reductions in emissions, improved combustion stability, and enhanced carbon capture performance [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on applying oxy-fuel combustion to an industrial boiler, Ahn et al [16] compared air combustion and oxy-fuel combustion in the combustion chamber of a furnace-type boiler and showed that retrofitting was possible by replacing the burner. Introducing flue gas recirculation (FGR) into an oxy-fuel boiler offers several benefits, including reductions in emissions, improved combustion stability, and enhanced carbon capture performance [17].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned studies [16][17][18][19][20][21] focused on the combustion chamber's flame and heat transfer characteristics. However, to successfully retrofit oxy-fuel combustion into existing industrial boilers, it is essential to consider heat transfer in components beyond the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…At the combustion of fossil fuels, not only emerging pollutants [1] to [4] and [6], [7] are closely monitored, but also other indicators that characterize the quality of the combustion process. At the combustion of coal, such indicator is e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While combusting various fuels in boilers and other engineering facilities, not only pollutants (Ahn et al, 2010;Čarnogurská et al, 2012;Moroń et al, 2013), but also other indicators that characterise the quality of the combustion process are thoroughly monitored. Such an indicator is, for example, the quality (composition) of ashes during coal combustion.…”
Section: Introductionmentioning
confidence: 99%